2017
DOI: 10.1007/s40808-017-0286-z
|View full text |Cite
|
Sign up to set email alerts
|

GIS-based land suitability evaluation for building height construction using an analytical process in the Mashhad city, NE Iran

Abstract: The user has requested enhancement of the downloaded file.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The spatial analysis of urban topography in geographical information system (GIS) indicated that the mean elevation values vary between 920 and 1340 m above sea level in northeast and southwest, respectively. In recent years, Mashhad city has been considered as an exciting research case of development modeling such as simulating urban growth (Rafiee et al 2009), building height construction modeling (Mansouri Daneshvar et al 2017a), carrying capacity of urban green spaces (Mansouri Daneshvar et al 2017b), urban transportation modeling (Bikdeli et al 2017), urban sprawl modeling (Rabbani et al 2017), and urban flexibility (Sarvari and Esnaashari 2018). Besides, the present paper focuses on hybrid modeling to assess the sprawl effects on climate parameters.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial analysis of urban topography in geographical information system (GIS) indicated that the mean elevation values vary between 920 and 1340 m above sea level in northeast and southwest, respectively. In recent years, Mashhad city has been considered as an exciting research case of development modeling such as simulating urban growth (Rafiee et al 2009), building height construction modeling (Mansouri Daneshvar et al 2017a), carrying capacity of urban green spaces (Mansouri Daneshvar et al 2017b), urban transportation modeling (Bikdeli et al 2017), urban sprawl modeling (Rabbani et al 2017), and urban flexibility (Sarvari and Esnaashari 2018). Besides, the present paper focuses on hybrid modeling to assess the sprawl effects on climate parameters.…”
Section: Study Areamentioning
confidence: 99%
“…In the second step, analytical network process (ANP) proposed by Saaty (1980Saaty ( , 2001 as a nonlinear structure with bilateral relationships is considered to detect factors' weights. According to Mansouri Daneshvar et al (2017a), the application of ANP can be described in some steps. Firstly, the construction of a conceptual model is produced to determine relationships between criteria.…”
Section: A Hybrid Model Of Factor Analysis and Analytical Network Process (F'anp)mentioning
confidence: 99%
“…The complete pairwise comparison matrix includes the relative importance of factors. Therefore, it is also possible to determine the degree of consistency that is used in developing the judgments (Mansouri Daneshvar et al 2017a).…”
Section: Pairwise Comparison Matrix Of Ahpmentioning
confidence: 99%
“…Spatial techniques and quantitative models integrate the concept of ranking and weighting the suitability classes during multi-criteria evaluation. Multi-criteria evaluation methods employ a number of qualitative or statistical methods, such as analytical hierarchy process (AHP), analytical network process (ANP), logistic regression (LR), multivariate statistical approach (MSA), weighted linear combination (WLC), and ordered weighted average (OWA) (Gong et al 2012;Ferretti and Pomarico 2013a;Mansouri Daneshvar et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…The method enables to handle massive geospatial issues related to land use suitability, site selection and resource evaluation isssues. Generally, it can provide immeasurable opportunities for land use planning and management problem [10]. MCDA allow to consider both qualitative and quantitative basis that assis the decision maker's judgment to be specific and to choose optimal choice based on a scientific technique.…”
Section: Introductionmentioning
confidence: 99%